Association of Genetic Polymorphisms in the Human FTO Gene and Obesity: Systematic Review and Meta-Analysis - Md Nor, Norazmir; Mohd Ruhaiddin, Nur Qairunnazirah; Khalid, Muhamad Shukry Khalid; Fikri, Al Mukhlas; Mohd Asmawi, Ummi Mohlisi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
The aim of the study is to perform a systematic review and meta-analysis to determine whether the Fat Mass and Obesity-associated (FTO) polymorphisms influenced obesity and which Single Nucleotide Polymorphisms (SNPs) raised the risk of obesity. We used PUBMED, SCOPUS, and Web of Science to identify studies investigating the association between genetic polymorphisms in the FTO gene and obesity. We discovered 16 studies that included 4,381 obese people and 5,652 healthy control people. Five genetic polymorphisms showed significant association with increased obesity risk in the allelic model: rs9939609 (OR=1.38, 95% CI:1.27−1.50: I²=0%, p<0.001), rs8050136 (OR=1.23, 95% CI:1.03−1.46: I²=54%, p=0.02), rs3751812 (OR=1.31, 95% CI:1.18−1.45: I²=4%, p<0.001), rs1421085 (OR=1.29, 95% CI: 1.14−1.46: I²=4%, p<0.001) and rs1121980 (OR=1.45, 95% CI: 1.10−1.93: I²=66%, p=0.009). For the allelic model, no significant correlation was identified in the rs15588902 SNP FTO gene (OR=1.24, 95% CI:0.96−1.62: I²=62%, p=0.11). Therefore, this meta-analysis found six FTO SNPs linked to human FTO polymorphisms and the risk of obesity. Further research on the FTO gene and obesity should consider gene-gene and gene-environment interactions.